New Advances in Chronic Kidney Disease: Biology, Diagnosis and Therapy - Susana Coimbra; Alice Santos-Silva (Biomedicines)
Chronic kidney disease (CKD) is characterized by a progressive and usually irreversible deterioration of renal function [...]